Relatives' knowledge of decision making in intensive care. Issue 5 (5th October 2004) - Booth, M G; Doherty, P; Fairgrieve, R; Kinsella, J
Abstract : Background/Aim: The law on consent has changed in Scotland with the introduction of the Adults with Incapacity (Scotland) Act 2000. This Act introduces the concept of proxy consent in Scotland. Many patients in intensive care are unable to participate in the decision making process because of their illness and its treatment. It is normal practice to provide relatives with information on the patient's condition, treatment, and prognosis as a substitute for discussion directly with the patient. The relatives of intensive care patients appeared to believe that they already had the right to consent on behalf of an incapacitated adult. The authors' aim was to assess the level of knowledge among relatives of intensive care patients of both the old and new law using a structured questionnaire. Methods: The next of kin of 100 consecutive patients completed a structured questionnaire. Each participant had the questions read to them and their answers recorded. Patients were not involved in the study. Results: Few (10%) were aware of the changes. Most (88%) thought that they previously could give consent on behalf of an incapacitated adult. Only 13% have ever discussed the preferences for life sustaining treatment with the patient but 84% felt that they could accurately represent the patient's wishes. Conclusions: There appeared to be a lack of public awareness of the impending changes. The effectiveness of the Act at improving the care of the mentally incapacitated adult will depend largely on how successful it is at encouraging communication and decision making in advance of incapacity occurring.